2022
DOI: 10.1093/oxfimm/iqac006
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID: a narrative review of the clinical aftermaths of COVID-19 with a focus on the putative pathophysiology and aspects of physical activity

Abstract: The pandemic coronavirus disease 2019 (COVID-19) can cause multi-systemic symptoms that can persist beyond the acute symptomatic phase. The post-acute sequelae of COVID-19 (PASC), also referred to as Long COVID, describe the persistence of symptoms and/or long-term complications beyond four weeks from the onset of the acute symptoms and are estimated to affect at least 20% of the individuals infected with SARS-CoV-2 regardless of their acute disease severity. The multi-faceted clinical picture of Long COVID en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 175 publications
0
20
0
Order By: Relevance
“…Notably, we observed no discrepancies between patients with PCC and control participants in exercise intensity corresponding to VT and onset of blood lactate accumulation at 4 mmol, indicating undisturbed metabolic exercise response at baseline and at the 48-hour follow-up. Previous suggestions that earlier lactate accumulation, possibly due to peripheral mitochondrial dysfunction leading to premature conversion to anaerobic glycolysis, occurs in the context of PCC and other postviral diseases have not been conclusively proven . Two reports found decreased VT and increased lactate levels after COVID-19, whereas other studies found no difference in VT between patients with PCC and control participants .…”
Section: Discussionmentioning
confidence: 93%
“…Notably, we observed no discrepancies between patients with PCC and control participants in exercise intensity corresponding to VT and onset of blood lactate accumulation at 4 mmol, indicating undisturbed metabolic exercise response at baseline and at the 48-hour follow-up. Previous suggestions that earlier lactate accumulation, possibly due to peripheral mitochondrial dysfunction leading to premature conversion to anaerobic glycolysis, occurs in the context of PCC and other postviral diseases have not been conclusively proven . Two reports found decreased VT and increased lactate levels after COVID-19, whereas other studies found no difference in VT between patients with PCC and control participants .…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has proposed that several phenotypes and distinct sub-diagnoses might exist under the umbrella of Long COVID, some of which with little immunological contribution ( 19 , 90 , 91 ). Since the post-acute sequelae of COVID-19 can most certainly not be attributed to a single pathophysiological mechanism ( 18 ), it is conceivable that a Treg dysregulation contributes to a Long COVID-associated immunopathology in multiple ways ( Figure 4 ), as it has also been suggested in other viral infections. For instance, the investigation of patients infected with hepatitis C virus (HCV) showed that those with chronic infections and HCV persistence exhibited higher Treg levels than recovered subjects ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it bears noting that the overall prevalence and types of symptoms can vary depending on the COVID-19 disease severity. Specifically, the proportion of patients that experience residual symptoms appears to be higher among previously hospitalized patients (16)(17)(18). In addition, the results of a clustering analysis conducted as a part of the REACT-2 study suggest that patients with severe initial symptoms report post-acute respiratory symptoms more often than those with mild or asymptomatic COVID-19 whose symptomatology is rather fatigue-dominant (19).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with cardiovascular magnetic resonance imaging suggest a complex picture with ischaemic and inflammatory signs in noninvasive tissue characterization [ 52 , 53 ]. The cause of such a persistent injury is ultimately unclear, and diverse hypotheses have been proposed, including immunological aberrations, autoimmunity, a change in the patient’s microbiome, metabolic dysregulation and microvascular, endothelial or hormonal dysfunctions [ 35 , 54 , 55 , 56 ]. Post-COVID is a multifactorial disease in which microvascular perfusion disturbances and inflammation may be most important denominators for cardiac dysfunction [ 49 ].…”
Section: Strain In the Diagnostic Work-up Of Post-covid Syndromementioning
confidence: 99%